2016
DOI: 10.3390/ijerph13070722
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Effect of Ambient Temperature on Mortality in Wuhan, China: A Time-Series Study Using a Distributed Lag Non-Linear Model

Abstract: Less evidence concerning the association between ambient temperature and mortality is available in developing countries/regions, especially inland areas of China, and few previous studies have compared the predictive ability of different temperature indictors (minimum, mean, and maximum temperature) on mortality. We assessed the effects of temperature on daily mortality from 2003 to 2010 in Jiang’an District of Wuhan, the largest city in central China. Quasi-Poisson generalized linear models combined with both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 42 publications
3
55
0
Order By: Relevance
“…Distributed lag nonlinear model has been widely used in the analysis of the burden of ambient air pollution on years of life lost, effects of ambient temperature on stroke hospital admissions, short-term effect of ambient temperature on mortality, and so on. [23][24][25] Furthermore, DLNM has also been used in the study of associations between meteorological factors and communicable diseases. Xiang et al 26 found reversed U-shaped nonlinear associations between ambient temperature, relative humidity, extreme wind velocity, and dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Distributed lag nonlinear model has been widely used in the analysis of the burden of ambient air pollution on years of life lost, effects of ambient temperature on stroke hospital admissions, short-term effect of ambient temperature on mortality, and so on. [23][24][25] Furthermore, DLNM has also been used in the study of associations between meteorological factors and communicable diseases. Xiang et al 26 found reversed U-shaped nonlinear associations between ambient temperature, relative humidity, extreme wind velocity, and dengue.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology rests on the definition of a crossbasis, a bi-dimensional space of functions describing the dependency along the space of the predictor and along lags. Therefore, DLNM can simultaneously investigate the non-linear exposure-response relationships and delayed effects in a flexible way and it has been widely used to examine the relationships and delayed effects of meteorological variables on human health [20,21] and has been widely used in various diseases [22][23][24][25][26][27][28]. Also the quasi-Poisson generalised linear regression, as a link function, was used to try to avoid the overdispersion problems of data.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted in the capital city of Hubei Province, central China—Wuhan. Known as the largest city in central China, Wuhan is located in the middle of the Yangzi River and has a typical subtropical monsoon climate [ 26 , 27 ]. Two urban districts, namely Jiang’an and Qiaokou, were selected as the study area, with a total of about 1.22 million permanent residents in 2010 and an urban area of 111.7 km 2 .…”
Section: Methodsmentioning
confidence: 99%